ISSUES OF DEVELOPMENT OF PROFESSIONAL COMPETENCES IN TEACHING SPECIALIZED SUBJECTS IN TECHNICAL HIGHER EDUCATION INSTITUTIONS - Ogalikov Mirzaakbar Botiralievich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article presents some problems in the teaching of specialized subjects in technical higher education institutions, ways to solve them, and recommendations for the development of student's professional skills.